Modulation of leaf attributes and water use efficiency in Quercus suber along a rainfall gradient - Gouveia, António C.; Freitas, Helena (Trees, 2008)
The aim of our study was to assess the intraspeciﬁc variation of a range of leaf attributes and carbon isotope discrimination (D), in Quercus suber, along an 800 mm rainfall gradient in Portugal. We measured speciﬁc leaf area (SLA), leaf thickness (LT) and density, and used leaf carbon isotope content as an integrated record of water use efﬁciency. The values of SLA of Q. suber were strongly, positively correlated with rainfall, decreasing as rainfall decreased. This reduction was mainly driven by LT, which was tightly correlated with SLA (R = -0.80, P\0.001), and steadily increased with declining rainfall. The signiﬁcant increase in carbon isotope discrimination towards the wetter end of the gradient, with a difference of 4.2% in D between the two extremes, suggests a strong adjustment of leaf gas exchange to water availability. Leaf changes associated with precipitation in Q. suber thus seem to inﬂuence water economy, since reduction of SLA with the increase of LT with aridity improves water use efﬁ- ciency. These data suggest that this evergreen tree species relies on its foliage plasticity and physiology to overcome water shortage.
Keywords: carbon isotope discrimination; carbon isotope discrimination á; evergreen tree; evergreen tree á; leaf plasticity; leaf plasticity á; rainfall gradient

Modulation of leaf attributes and water use efficiency in Quercus suber along a rainfall gradient - Gouveia, António C.; Freitas, Helena (Trees, 2008)
The aim of our study was to assess the intraspeciﬁc variation of a range of leaf attributes and carbon isotope discrimination (D), in Quercus suber, along an 800 mm rainfall gradient in Portugal. We measured speciﬁc leaf area (SLA), leaf thickness (LT) and density, and used leaf carbon isotope content as an integrated record of water use efﬁciency. The values of SLA of Q. suber were strongly, positively correlated with rainfall, decreasing as rainfall decreased. This reduction was mainly driven by LT, which was tightly correlated with SLA (R = -0.80, P\0.001), and steadily increased with declining rainfall. The signiﬁcant increase in carbon isotope discrimination towards the wetter end of the gradient, with a difference of 4.2% in D between the two extremes, suggests a strong adjustment of leaf gas exchange to water availability. Leaf changes associated with precipitation in Q. suber thus seem to inﬂuence water economy, since reduction of SLA with the increase of LT with aridity improves water use efﬁ- ciency. These data suggest that this evergreen tree species relies on its foliage plasticity and physiology to overcome water shortage.
Keywords: carbon isotope discrimination; carbon isotope discrimination á; evergreen tree; evergreen tree á; leaf plasticity; leaf plasticity á; rainfall gradient